2019
DOI: 10.36082/qjk.v13i2.80
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pelatihan Tedi’s Behavior Change Model pada Guru dan Orang Tua terhadap Keterampilan Menggosok Gigi Anak Prasekolah

Abstract: Abstrak Masalah kesehatan gigi anak prasekolah lebih tinggi dibandingkan dengan sekolah dasar, hal ini disebabkan anak belum mampu melakukan aktivitas mandiri dalam menggosok gigi. Strategi perubahan perilaku yang tepat dapat dilakukan dengan memberikan pendidikan kesehatan gigi oleh orang tua dan guru menggunakan metode dan media pembelajaran disesuaikan perkembangan anak. Pelatihan tedi’s behavior change pada guru dan orang tua merupakan model pembelajaran menggosok gigi dalam upaya pembentukan perilak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 11 publications
0
14
0
12
Order By: Relevance
“…Strengthened by Purnama et al states that facility support is one of the successes of the dental health program in schools.Sari et al research proves that brushing skills can also affect oral and dental hygiene. 6,21,22 Reinforced by Arianto et al that proper and correct brushing skills are quite important factors for oral and dental hygiene. Another opinion of Putri et al also states that brushing teeth is a mechanical way to clean plaque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strengthened by Purnama et al states that facility support is one of the successes of the dental health program in schools.Sari et al research proves that brushing skills can also affect oral and dental hygiene. 6,21,22 Reinforced by Arianto et al that proper and correct brushing skills are quite important factors for oral and dental hygiene. Another opinion of Putri et al also states that brushing teeth is a mechanical way to clean plaque.…”
Section: Discussionmentioning
confidence: 99%
“…During childhood, these conditions will have an impact on their growth and development and have an impact on their future lives. [5][6][7] The high rate of oral and dental disease in preschool children is strongly influenced by several factors. The main factors causing caries are the host (teeth and saliva), microorganisms, substrate and added time factor.Another factor knowledge, attitudes and behavior of parents in maintaining the health of their children's teeth and mouth.Bad oral and dental hygiene causes the accumulation of plaque which contains various kinds of bacteria, including streptococcus mutans as the main cause of caries.…”
Section: Introductionmentioning
confidence: 99%
“…Behavior based on correct knowledge will last longer than behavior without knowledge, including knowledge about how to maintain proper dental health will greatly affect the incidence of caries. 6,9 This is evidenced by the results of research by Sari et al (2015) showing that knowledge of oral health is related to the oral hygiene index, where the better the level of knowledge, the better the OHI-S index. Another study, Yohanes et al (2013) showed that children who had good knowledge had a 2.2 times chance of having good oral and dental hygiene status.…”
Section: Introductionmentioning
confidence: 92%
“…Gigi yang berlubang yang tidak dirawat akan menyebabkan masalah sistemik selama kehamilan dan dapat menyebabkan kelahiran prematur dan berat bayi rendah (Suwandi, 2019). Sebagian besar masyarakat belum mengetahui status kesehatannya dikarenakan karena perilaku pemeliharan kesehatan gigi yang masih rendah (Purnama et al, 2019).…”
Section: Pendahuluanunclassified